2006
DOI: 10.1007/bf02984657
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2-deoxy-2-[18F]fluoro-D-glucose positron emission tomography in gastric carcinoma: relation to histological subtypes, depth of tumor invasion, and glucose transporter-1 expression

Abstract: This study provided important information on the clinical application of FDG-PET in gastric carcinoma that early or non-cohesive gastric carcinoma may show lower FDG uptake. Therefore, the usefulness of FDG-PET for the detection of gastric carcinoma is limited. But there is a possibility that FDG uptake associated with GLUT-1 expression may serve as a prognostic factor of gastric carcinoma representing tumor metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
75
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 19 publications
12
75
2
2
Order By: Relevance
“…In the present study, 42% of GSRCs had detectable FDG uptake on PET by visual analysis, and GSRCs with membranous GLUT-1 expression showed significantly higher FDG uptakes than those with cytoplasmic expression, which suggests that the degree of FDG uptake is affected by GLUT-1 expression in signet ring cells. These results are consistent with those of previous studies [19,24] that examined the relation between FDG uptake and GLUT-1 expression in gastric cancer.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, 42% of GSRCs had detectable FDG uptake on PET by visual analysis, and GSRCs with membranous GLUT-1 expression showed significantly higher FDG uptakes than those with cytoplasmic expression, which suggests that the degree of FDG uptake is affected by GLUT-1 expression in signet ring cells. These results are consistent with those of previous studies [19,24] that examined the relation between FDG uptake and GLUT-1 expression in gastric cancer.…”
Section: Discussionsupporting
confidence: 93%
“…Degree of GLUT-1 expression has previously been shown to be correlated with increased FDG uptake in a [20]. In another study by Yamada et al, noncohesive gastric cancer was found to show significantly lower GLUT-1 expression and FDG uptake than the cohesive type [24]. De Potter et al also reported that only 25% of GSRCs had FDG avidity in a small group study (n=8) [21], which concurs with that found in the Korean population [22].…”
Section: Discussionsupporting
confidence: 71%
“…Thus FDG-PET/CT will not replace endoscopy in this patient group and these techniques are complementary. There are a variety of malignant tumours which might be FDG-negative and consequently missed by FDG-PET/CT, such as bronchoalveolar carcinomas, neuroendocrine tumours, low-grade sarcomas or signet ring cell adenocarcinomas [21][22][23]. In our experience the CT part of the PET/ CT study can partially help to overcome this limitation by showing suspicious morphological changes.…”
Section: Discussionmentioning
confidence: 89%
“…GLUT1 is ubiquitously expressed in almost all cell types, but is frequently overexpressed in malignant tissue, leading to the intracellular accumulation of FDG, which can then be visualized by FDG-PET. In gastric carcinoma, GLUT1 is expressed late in carcinogenesis, and increased amounts are associated with tumor progression and patient survival [7][8][9]. Kawamura et al [7] analyzed GLUT1 protein expression in 617 carcinomas and 50 tubular adenomas of the stomach.…”
Section: Differences Of Histology and Glucose Transporter 1 Expressiomentioning
confidence: 99%
“…Yamada et al [8] evaluated the association between FDG uptake and histopathological type in 40 patients with gastric carcinoma among whom 19 patients (48%) showed detectable FDG uptake. Cohesive carcinomas (papillary adenocarcinoma, tubular adenocarcinoma, and solid-type poorly differentiated adenocarcinoma) were more significantly detectable than non-cohesive carcinomas (signet-ring cell carcinoma and non-solid type poorly differentiated carcinoma) (65 vs. 14%, respectively).…”
Section: Differences Of Histology and Glucose Transporter 1 Expressiomentioning
confidence: 99%